A prospective study of erythrocyte polyunsaturated fatty acid, weight gain, and risk of becoming overweight or obese in middle-aged and older women - Wang, Lu (Eur J Nutr, 2015)
PURPOSE: ω3 and ω6 fatty acid (FA) may have divergent effects on the development of obesity. We examined the association of baseline erythrocyte ω3 and ω6 FA composition with body weight change and the risk of becoming overweight or obese in the Women's Health Study (WHS) participants. METHODS: We identified 534 women who had baseline erythrocyte FA measured and a baseline body mass index (BMI) of 18.5 to <25 kg/m(2). Body weight was updated at a total of 6 time points during follow-up. RESULTS: Weight gain during a mean of 10.4-y follow-up increased with increasing quartiles of erythrocyte cis ω6 FAs, ω6/ω3 ratio and trans FAs while decreased with increasing cis ω3 FAs. After multivariable adjustment including total energy intake and physical activity, the weight gain (kg) in the highest vs. the lowest quartile was 3.08 vs. 2.32 for erythrocyte cis ω6 FAs (P(trend): 0.04), 2.07 vs. 2.92 for cis ω3 FAs (P(trend): 0.08), 2.93 vs. 2.05 for ω6/ω3 ratio (P(trend): 0.046), and 3.03 vs. 2.27 for trans FAs (P(trend): 0.06). Among individual FA, the associations were significant for 18:2ω6, 18:3ω6, and trans 18:1 and marginally significant for 20:3ω6 and trans 18:2. The risk of becoming overweight or obese (defined as BMI ≥25 kg/m(2) at any follow-up time point) increased across increasing ω6/ω3 ratio (multivariable model P(trend): 0.04). CONCLUSIONS: In this prospective study, we found suggestive evidence that erythrocyte cis ω6 FAs may be positively associated, and cis ω3 FAs inversely associated with weight gain in initially normal-weight women.